2012
DOI: 10.1088/0741-3335/54/11/113001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Spheromak Physics Experiment (SSPX): design and physics results

Abstract: The Sustained Spheromak Physics Experiment (SSPX) was a high-temperature (T e up to 0.5 keV) spheromak formed by coaxial helicity injection (CHI) and with plasma duration of a few milliseconds following the high-current formation stage. Clean walls and low impurity operation were obtained by a combination of baking, discharge cleaning and titanium deposition on the walls, allowing the generation of high-quality plasmas. Resistive-magnetohydrodynamic simulations, benchmarked to the experiment, were used to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 72 publications
(145 reference statements)
1
19
0
Order By: Relevance
“…While the helicity injection from a single CHI has proven to be a robust method not only for the formation but also for the sustainment of related configurations, [7][8][9] the requirement of auxiliary current drive and heating schemes, such as rf and neutral beam injection, is foreseen in order to achieve high temperatures and good particle confinement. 4,6 This is because the current drive by helicity injection relies on the tendency of the plasma to relax, and this necessarily involves MHD fluctuations that could degrade the confinement.…”
Section: A Description Of the Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the helicity injection from a single CHI has proven to be a robust method not only for the formation but also for the sustainment of related configurations, [7][8][9] the requirement of auxiliary current drive and heating schemes, such as rf and neutral beam injection, is foreseen in order to achieve high temperatures and good particle confinement. 4,6 This is because the current drive by helicity injection relies on the tendency of the plasma to relax, and this necessarily involves MHD fluctuations that could degrade the confinement.…”
Section: A Description Of the Configurationmentioning
confidence: 99%
“…In this sense, the ST-PCC may be regarded as a combination of a FCS and a conventional gun spheromak. [7][8][9] Tang and Boozer 4 studied these configurations under the assumption of complete relaxation 5,10 and showed that their magnetic structure is primarily determined by four factors: (1) the flux amplification factor [see Eq. (4)], (2) the elongation of the cylinder, (3) the requirement of stability to the tilt mode, and (4) the vacuum bias flux imposed by a set of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…All the cases presented use uniform density; however, calculations that use uniform temperature for the same pressure profile exhibit similar behavior. 13 The parameters of our straight-spheromak computations are based on conditions achieved in SSPX, 15 where consistency of pressure profiles before and after MHD activity imply a pressure-driven limit. 25 We list the dimensional parameters in Table I The safety factor q and normalized parallel current, a = µ 0 aJ || /B, profiles of our straight-spheromak equilibria are shown in Figure 14.…”
Section: Linear Analysis Of Straight Spheromak Equilibriamentioning
confidence: 99%
“…Our study was initially motivated by an interest 13 in interchange modes in the Sustained Spheromak Physics Experiment (SSPX). 14,15 Thus, we also consider drift stabilization of interchange in cylindrical screw-pinch equilibria with parameters based on SSPX. Jardin first used this class of equilibria to map out the ideal stability boundaries of spheromaks.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear self-stabilization. The idea of a nonlinearly saturated kink-unstable flux rope figures strongly in the spheromak literature, for example on SPHEX [39] and SSPX [40], and is arguably relevant to single helicity helical axis states in reversed field pinches [41]. When we program the RSX experimental current ramp so that the kink instability grows and the axial flow [34] causes the twisted column to gyrate, it appears to 'screw' into the external anode boundary.…”
Section: Single Flux Ropementioning
confidence: 99%